THE INFLUENCE OF PRICE PERCEPTION AND ELECTRONIC WORD OF MOUTH ON CONSUMER PURCHASE DECISION THROUGH E-COMMERCE IN MALANG CITY (STUDY AT SHOPEEFOOD SERVICES IN SHOPEE E-COMMERCE) - Cholista Ferry Irawan; Rachman Hartono; Silvana Maulidah; Riyanti Isaskar (Socio-Economics/Agribusiness Department, 2023)
Technological developments in the era of globalization have provided changes for society both in social, economic, and cultural aspects. This massive technological development has created unprecedented new job and business opportunities. One of the business potentials created by the massive development of information technology is the emergence of a business opportunity through e-commerce. This study focuses on the Shopeefood service. This study's objective was to investigate the influence of price perception